THE IMPACT OF USING AUDIO-VISUAL AIDS ON TEACHING LISTENING AMONG IRANIAN PRE-INTERMEDIATE EFL LEARNERS - Namaziandost, Ehsan; Nasri, Mehdi (LLT Journal: A Journal on Language and Language Teaching, 2019)
The present study aimed to investigate the effects of audio-visual aids on teaching listening among Iranian pre-intermediate EFL learners. In order to fulfill the objectives of the study, the researcher selected 40 homogeneous pre-intermediate students and divided them into two equal groups. The two groups were the experimental groups (n=20) and a control groups (n=20). Then a listening comprehension pre-test was administered to assess the participants' listening comprehension at the beginning of the course. After the pre-test, the researcher practiced the treatment on the experimental groups. During the treatment sessions, The EG was taught by using authentic video, while the CG used audio Compact Disc (CD) as the teaching aid most often used by ESL teachers in teaching listening. After the treatment which took 15 sessions, the researcher administered a post-test to find out the effect of audio-visual aids on teaching listening. When the data were collected, Independent and Paired Samples T-tests were run to analyze them. The results showed that the EG students taught by using authentic video achieved higher results in listening than the CG ones taught by audio compact disc (CD). The implications of the study suggest that using audio-visual aids can help EFL learners to develop their listening comprehension.DOI: 10.24071/llt.2019.220209